The Culprit Fay, and Other Poems - Drake, Joseph Rodman, 1795-1820 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Culprit Fay, and Other Poems by Joseph Rodman Drake" is a collection of poems written in the early 19th century, during the Romantic era. The book features a variety of works, with a central focus on themes of nature, love, and the supernatural, embodying the essence of the literary movements of its time. Among its standout pieces is the narrative poem "The Culprit Fay," which draws readers into a whimsical world of fairies and enchantment. In "The Culprit Fay," the story revolves around a fairy who has broken the sacred laws of his realm by falling in love with a mortal woman. As a result, he is summoned to face judgment by the fairy court, where he learns of his punishment: he must embark on a quest to redeem himself by retrieving a magical drop from a sturgeon and igniting his flamewood lamp once again. The poem captures the struggle and adventure of the Fay, detailing his encounters with water sprites and his ultimate triumph. Other poems in the collection complement this narrative, exploring the beauty of nature, reflections on human emotion, and patriotic themes, all crafted with Drake's lyrical style and rich imagery. (This is an automatically generated summary.)
Release date is 1995-08-01
Transcribed from the 1836 George Dearborn edition by David Price
Keywords: American poetry -- 19th century; Fairies -- Poetry; New York (State) -- Poetry